2003
DOI: 10.1007/s00198-003-1407-2
|View full text |Cite
|
Sign up to set email alerts
|

Phalangeal quantitative ultrasound technology and dual energy X-ray densitometry in patients with primary hyperparathyroidism: influence of sex and menopausal status

Abstract: Fifty-one patients with surgically proven primary hyperparathyroidism (PHPT), 11 males and 40 females, mean age+/-SD: 55.9+/-14.1 years, and 58 age- and sex-matched normal subjects were studied. The femoral and L(2)-L(4) bone mineral density (BMD; Hologic QDR 4500 C), as well as quantitative ultrasonometry (QUS; DBM-Sonic 1200) of the phalanges of both hands were measured in patients and controls. QUS measurements included amplitude-dependent speed of sound (AD-SoS), and other parameters derived from the graph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 30 publications
2
15
0
Order By: Relevance
“…All subjects underwent osteodensitometry using dual‐energy absorptiometry (DXA) (Hologic QDR 4500 C, Waltham, MA, USA) with measurement of BMD at the lumbar spine and femoral neck, and a T‐score was calculated. The long‐term coefficient of variation of the DXA measurements was 0.56%, using Hologic anthropometric spine phantom 9 …”
Section: Methodsmentioning
confidence: 99%
“…All subjects underwent osteodensitometry using dual‐energy absorptiometry (DXA) (Hologic QDR 4500 C, Waltham, MA, USA) with measurement of BMD at the lumbar spine and femoral neck, and a T‐score was calculated. The long‐term coefficient of variation of the DXA measurements was 0.56%, using Hologic anthropometric spine phantom 9 …”
Section: Methodsmentioning
confidence: 99%
“…The study population was obtained from a cohort of 236 postmenopausal women who underwent serial measurements of bone mass by osteodensitometry using dual energy X‐ray absorptiometry (DXA) (Hologic QDR 4500 C, Waltham, MA, USA) with measurement of BMD at the lumbar spine and hip. The long‐term coefficient of variation of the DXA measurements was 0.56%, using Hologic anthropometric spine phantom 4 …”
Section: Methodsmentioning
confidence: 99%
“…[10] Further, present study recorded significant difference between the parathyroid hormones of postmenopausal women and premenopausal women which are very similar to the findings of the previous studies of Cammozi V et al and Safi S et al in which they observed that parathyroid hormone was significantly low in postmenopausal women. [19,20] Parathyroid hormones gradually increased with the age in women and it has been found associated with increase turnover of bone. [21] Furthermore, there was an insignificant difference in calcitonin level of postmenopausal women and premenopausal women.…”
Section: Discussionmentioning
confidence: 99%